Comporative study of the city and periphery in the process of urbanization in Kazakhstan (Journal of Philosophy Culture and Political Science, 2018)
This article assesses the process of urbanization using an example of Kazakhstan. Also it examines the role of cities at the global level, and the impact on globalization. The authors consider the city as a basic element for social and economic development in comparative perspective. First, they analyze the impact of urban culture in the development of the dialogue of civilizations in Kazakhstan. Second, they analyze the demographic growth of the urban population and the problem of relationships between cities and peripheries. Third, they analyze cities as a new cultural phenomenon and organization of the cultural system focusing on similarities and differences of urban and rural culture. Key words: Kazakhstan, urbanization, city, periphery, culture